Roll core and solid-state battery

By setting the elastic layer of the transition area in the curl core of the solid battery, the problem of the solid electrolyte film is susceptible to the breakthrough, and the effect of the battery cycle performance is achieved.

CN222422023UActive Publication Date: 2025-01-28CHENGDU QINGTAO NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202422865540.8
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-28
Estimated Expiration
2034-11-25

AI Technical Summary

Technical Problem

The solid electrolyte membrane is prone to rupture in the winding part, resulting in a short circuit inside the battery.

Method used

Set the elastic layer in the transition area of ​​the solid electrolyte, and the curvature radius of the curvature radius of the transition area is less than the curvature radius of the bending area, and the flat area, the bending area, and the transition area of ​​the transition area are set on the length direction of the rolling core to improve the flexibility of the solid electrolyte film. And torture performance.

Benefits of technology

By improving the flexibility and deflection performance of the solid electrolyte, the risk of rupture the membrane during wrapping is reduced, thereby avoiding the short circuit inside the battery and improving the circulating performance of the solid -state battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222422023U_ABST
    Figure CN222422023U_ABST
Patent Text Reader

Abstract

The utility model relates to a roll core and a solid-state battery, and relates to the technical field of batteries. The roll core comprises a positive plate, a negative plate and a solid electrolyte membrane arranged between the positive plate and the negative plate, and the solid electrolyte membrane comprises a flat area, a bending area and a transition area for connecting the flat area and the bending area; the transition area comprises an elastic layer; the bending angle of the flat area in the length direction of the roll core is less than or equal to 3 degrees; the curvature radius of the transition area is smaller than that of the bending area; the length of the transition area in the length direction of the roll core is 1-10 mm. According to the invention, the elastic layer is arranged in the transition area which is easy to break, the curvature radius of the transition area is smaller than that of the bending area, and the length of the transition area in the length direction of the roll core is 1-10mm, so that the solid electrolyte membrane has excellent flexibility and flexural property, is not easy to break in the winding process and in the winding state, and has good application prospects. The solid-state battery is not easy to generate internal short circuit, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a roll-core, solid-state battery. Background Art

[0002] Lamination and winding are two commonly used battery cell forming processes. However, since the solid electrolyte itself is not flexible and there is almost no adhesion between the solid electrolytes, the solid electrolyte layer is prone to rupture in the winding part. When the solid electrolyte layer ruptures, the positive and negative electrodes come into contact with each other, causing a short circuit inside the battery. Utility Model Content

[0003] Based on this, it is necessary to provide a roll-core, solid-state battery to solve the technical problem that the solid electrolyte membrane is prone to rupture and cause battery short circuit.

[0004] The specific solution of this application to solve the above technical problems is as follows:

[0005] The first aspect of the present application provides a winding core, which includes a positive electrode sheet, a negative electrode sheet, and a solid electrolyte membrane disposed between the positive electrode sheet and the negative electrode sheet, wherein the solid electrolyte membrane includes a flat area, a bending area, and a transition area connecting the flat area and the bending area; the transition area includes an elastic layer; wherein,

[0006] The bending angle of the flat area in the length direction of the winding core is ≤3°;

[0007] The curvature radius of the transition zone is smaller than the curvature radius of the bending zone;

[0008] The length of the transition zone in the longitudinal direction of the winding core is 1 mm to 10 mm.

[0009] In some embodiments, the solid electrolyte membrane has a thickness of 1 μm to 100 μm.

[0010] In some embodiments, the thickness of the elastic layer gradually increases from the outer layer to the inner layer of the winding core.

[0011] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer; the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer;

[0012] The positive electrode active material layer is arranged on both sides of the positive electrode current collector, and the negative electrode active material layer is arranged on both sides of the negative electrode current collector.

[0013] In some embodiments, in each layer of the winding core, the area of ​​the elastic layer accounts for 5% to 30% of the sum of the areas of the transition zone and the bending zone.

[0014] In some embodiments, in each layer of the winding core, the thickness of the flat region, the transition region, and the bending region are the same.

[0015] In some embodiments, the length of the transition zone in the length direction of the winding core gradually decreases from the outer layer to the inner layer of the winding core.

[0016] In some embodiments, the flat regions have the same area from the outer layer to the inner layer of the winding core, and the length of the bending region in the circumferential direction of the winding core gradually decreases.

[0017] In some embodiments, the number of winding layers of the core is 10 to 100.

[0018] A second aspect of the present application provides a solid-state battery, which includes the winding core provided by the first aspect above.

[0019] The present application arranges an elastic layer in the transition zone, and the curvature radius of the transition zone is smaller than the curvature radius of the bending zone. The length of the transition zone in the length direction of the winding core is 1mm~10mm, so that the solid electrolyte membrane has excellent flexibility and flexural properties in the transition zone, is not easy to break during the winding process and in the winding state, and is not easy to have an internal short circuit in the solid-state battery, thereby improving the cycle performance of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0021] In order to more completely understand the present application and its beneficial effects, the following description will be made in conjunction with the accompanying drawings. In the following description, the same reference numerals represent the same parts.

[0022] Figure 1 Schematic diagram of the overall structure of the winding core in one embodiment of the present application.

[0023] Figure 2 Schematic diagram of the structure of one end of a winding core in one embodiment of the present application.

[0024] Figure 3 This is a schematic diagram of the structure of a flattened solid electrolyte membrane in one embodiment of the present application.

[0025] Figure 4 This is a schematic structural diagram of one end of a winding core in another embodiment of the present application.

[0026] Description of Reference Numerals

[0027] 1. Flat area; 2. Transition area; 3. Bending area; Length direction A; Circumferential direction B. DETAILED DESCRIPTION

[0028] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0029] In the description of the present application, it should be understood that if the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. appear, the orientation or position relationship indicated by these terms is based on the orientation or position relationship shown in the accompanying drawings, which is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0030] In addition, if the terms "first" or "second" appear, these terms are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, if the term "plurality" appears, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0031] In this application, unless otherwise clearly specified and limited, if the terms "installed", "connected", "connected", "fixed" and the like appear, these terms should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integrated connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0033] It should be noted that if an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element. If an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.

[0034] See also Figure 1 to Figure 2 As shown, Figure 1 Schematic diagram of the overall structure of the winding core in one embodiment of the present application. Figure 2 Schematic diagram of the structure of one end of a winding core in one embodiment of the present application.

[0035] A first aspect of the present application provides a winding core, which includes a positive electrode sheet, a negative electrode sheet, and a solid electrolyte membrane disposed between the positive electrode sheet and the negative electrode sheet.

[0036] See also Figure 3-4 As shown, Figure 3 This is a schematic diagram of the structure of a flattened solid electrolyte membrane in one embodiment of the present application. Figure 4 The solid electrolyte membrane includes a flat region 1, a bending region 3, and a transition region 2 connecting the flat region 1 and the bending region 3; the transition region 2 includes an elastic layer.

[0037] In some embodiments, the bending angle of the flat area 1 in the length direction A of the winding core is ≤3°, including but not limited to 3°, 2°, and 1°.

[0038] The “bending angle” refers to the angle between the line connecting the highest point and the lowest point on the flat area 1 and the horizontal plane after the roll core is placed horizontally.

[0039] In some embodiments, the radius of curvature of the transition zone 2 is smaller than the radius of curvature of the bending zone 3 .

[0040] In some embodiments, the length of the transition zone 2 in the length direction A of the core is 1 mm to 10 mm, including but not limited to 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, and 10 mm.

[0041] In the present application, an elastic layer is arranged in the transition zone 2, the curvature radius of the transition zone 2 is smaller than the curvature radius of the bending zone 3, and the length of the transition zone 2 in the length direction A of the winding core is 1 mm to 10 mm, so that the solid electrolyte membrane has excellent flexibility and flexural properties in the transition zone 2, is not easy to break during the winding process and in the winding state, and the solid-state battery is not easy to have an internal short circuit, thereby improving the cycle performance of the solid-state battery.

[0042] In some embodiments, the thickness of the solid electrolyte membrane is 1 μm to 100 μm, including but not limited to 1 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, and 100 μm.

[0043] In some embodiments, the thickness of the elastic layer gradually increases from the outer layer to the inner layer of the winding core.

[0044] In some embodiments, the elastic layer includes polymer electrolyte particles, and the polymer electrolyte particles include one or more of polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinyl chloride (PVC), polyphenylene oxide (PPO), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO), polyvinylidene chloride (PVDC) and single-ion polymer electrolytes.

[0045] In some embodiments, in each layer of the winding core, the area of ​​the elastic layer accounts for 5% to 30% of the sum of the areas of the transition zone 2 and the bending zone 3, including but not limited to 5%, 10%, 15%, 20%, 25%, and 30%. In some embodiments, the elastic layer is filled with a conductor, the conductor includes a two-dimensional conductor, the two-dimensional conductor is graphite and / or graphene, and the graphite is selected from KS-6, KS-15, SFG-6, and SFG-15.

[0046] Two-dimensional conductors, such as graphite and graphene, have a better relative area and can provide a better electronic conduction path for the elastic layer, which is beneficial to promote charge transfer, thereby promoting the transmission of lithium ions and forming a good lithium ion and electron transmission channel between the positive and negative electrodes. On the other hand, graphite and graphene have better interlayer slip properties and can deform with the deformation of the solid electrolyte membrane, providing stress support for the elastic layer while preventing the membrane from tearing, so that the solid electrolyte membrane has both excellent mechanical flexural properties and electrochemical cycling performance.

[0047] In some embodiments, the conductor further comprises a one-dimensional conductor; the one-dimensional conductor is a carbon nanotube and / or a conductive fiber.

[0048] In some embodiments, the carbon nanotubes may be single-arm carbon nanotubes or multi-arm carbon nanotubes, or may include both single-arm carbon nanotubes and multi-arm carbon nanotubes.

[0049] In some embodiments, the conductive fibers may be selected from carbon-based fibers or conductive polymer fibers.

[0050] In the present application, the one-dimensional conductor and the two-dimensional conductor are co-distributed in the elastic layer, providing a multi-dimensional transmission channel for electrons, which can further promote the transmission of lithium ions, thereby improving the charge and discharge performance of the battery; and the one-dimensional conductor has a higher aspect ratio, and can be mixed and coordinated with the polymer chains in the elastic layer, which can further enhance the anti-flexing performance of the elastic layer and enhance the flexibility of the elastic layer.

[0051] In some embodiments, in each layer of the winding core, the thicknesses of the flat region 1 , the transition region 2 , and the bending region 3 are the same.

[0052] In some embodiments, the length of the transition zone 2 in the length direction A of the winding core gradually decreases from the outer layer to the inner layer of the winding core.

[0053] In some embodiments, from the outer layer to the inner layer of the winding core, the area of ​​the flat region 1 is the same, and the length of the bending region 3 in the circumferential direction B of the winding core gradually decreases.

[0054] In some embodiments, the flat region 1 includes a first bonding layer and first solid electrolyte particles, and the first solid electrolyte particles are filled in the first bonding layer.

[0055] In some embodiments, the bending region 3 includes a second bonding layer and second solid electrolyte particles, and the second solid electrolyte particles are filled in the second bonding layer.

[0056] In some embodiments, the first bonding layer is filled with first bonding particles, and the second bonding layer is filled with second bonding particles. The first bonding particles and the second bonding particles include soft segments and hard segments, respectively, and the hard segment content of the first bonding particles is greater than the hard segment content of the second bonding particles; wherein the soft segment includes a diene-based soft segment, and the hard segment includes a styrene-based hard segment.

[0057] In some embodiments, the content of the hard segment in the first binder particles is greater than 40% by mass of the first binder particles, and the content of the hard segment in the second binder particles is 20% to 34% by mass of the second binder particles.

[0058] In some embodiments, the first bonding particles and the second bonding particles are block polymers including A and B, wherein A is a compound having a structure of the following formula (I), and B is a compound having a structure of the following formula (II),

[0059] , .

[0060] Wherein, R1 to R3 in formula (I) and R1′ to R6′ in formula (II) are each independently selected from hydrogen or an alkyl group.

[0061] In some embodiments, the first adhesive layer and the second adhesive layer are both styrene-based adhesive layers.

[0062] In some of the embodiments, the styrene-based adhesive layer is a styrene-butadiene-styrene block polymer adhesive layer, a styrene-isoprene-styrene block polymer adhesive layer, or an α-methylstyrene-butadiene-α-methylstyrene block polymer adhesive layer.

[0063] In some embodiments, the hard segment content of the first bonding particles is greater than the hard segment content of the second bonding particles.

[0064] The present application provides the solid electrolyte membrane with higher flexibility by arranging the second bonding particles in the bending zone 3 with a lower hard segment content in the bonding layer of the bending zone 3 relative to the flat zone 1, thereby effectively resisting stress deformation and / or stress concentration that may occur in the bending zone 3, and further improving the anti-fragmentation performance of the solid electrolyte membrane.

[0065] In some embodiments, the first solid electrolyte particles and the second solid electrolyte particles are inorganic solid electrolyte particles.

[0066] It can be understood that in some other embodiments, the present application does not specifically limit the type of solid electrolyte. On the premise of satisfying the overall inventive concept of the present application, any known type of solid electrolyte can be applied to the present application. The following is only used as an illustrative example rather than a limitation on the scope of protection. The first solid electrolyte and the second solid electrolyte can be independently selected from one or more of oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, hydride solid electrolytes, boride solid electrolytes, and nitride solid electrolytes.

[0067] In some embodiments, the first solid electrolyte particles are the same as or different from the second solid electrolyte particles.

[0068] Specifically, the oxide solid electrolyte is composed of oxide solid electrolyte particles, and may include one or more garnet ceramics, LISICON type oxides, NASICON type oxides, and perovskite type ceramics. For example, one or more garnet ceramics may be selected from the group consisting of: Li 6.5 Ln3Z 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 La3Zr 1.75 Nb 0.25 O 12 , Li 6.75 La3Zr 1.75 Nb 0.25 O 12 and combinations thereof. One or more LISICON-type oxides may be selected from the group consisting of: Li14Zn(GeO4)4, Li 3+x (P 1-x Si x )O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1) and combinations thereof.

[0069] One or more NASICON-type oxides may be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example: in certain variations, one or more NASICON-type oxides may be selected from the group consisting of: Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1+x Al x Ti 2-x (PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li 1+x Y x Zr 2-x (PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1. 7(PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3 and combinations thereof.

[0070] One or more perovskite-type ceramics may be selected from the group consisting of: Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1. 3Ta 1.7 O9, Li 2x-y Sr1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25) and combinations thereof. In one variant, one or more oxide-based materials may have an ionic conductivity greater than or equal to about 10 -5 S / cm and less than or equal to about 10 -1 S / cm.

[0071] The sulfide solid electrolyte consists of sulfide solid electrolyte particles and may include one or more sulfide-based materials selected from the group consisting of: Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge, and Sn and 0 ≤ x ≤ 2), Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , Li 9.6 P3S 12 , Li7P3S 11 , Li9P3S9O3, Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 , Li(Ge 0.5 Sn 0.5 )P2S 12 , Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br, or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 , Li 3.25 Ge 0.25 P 0.75 , S4, Li 10 SnP2S 12 , Li10 SiP2S 12 、 Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 、 (1 - x)P2S 5-x Li2S (where 0.5 ≤ x ≤ 0.7) and combinations thereof. In one variation, one or more sulfide - based materials may have an ionic conductivity greater than or equal to about 10 -7 S / cm to less than or equal to about 1 S / cm.

[0072] Halide solid electrolytes may be composed of halide solid electrolyte particles, including Li2CdCl4, Li2MgCl4, Li2CdI4, Li2ZnI4, Li3OCl, LiI, Li5ZnI4, Li3OCl 1-x Br x (where 0 < x < 1) and combinations thereof. In one variation, one or more halide - based materials may have an ionic conductivity greater than or equal to about 10 -8 S / cm to less than or equal to about 10 -1 S / cm.

[0073] Hydride solid electrolytes are composed of hydride solid electrolyte particles. The hydride - based particles may include one or more hydride - based materials selected from the group consisting of: Li3AlH6, LiBH4, LiBH4 - Li X (where X is one of Cl, Br, and I), LiNH2, Li2NH, LiBH4 - LiNH2, and combinations thereof. In one variation, one or more hydride - based materials may have an ionic conductivity greater than or equal to about 10 -7 S / cm to less than or equal to about 10 -2 S / cm.

[0074] Boride solid electrolytes are composed of borate solid electrolyte particles, including one or more borate - based materials from the group consisting of: Li2B4O7, Li2O-(B2O3)-(P2O5), and combinations thereof. In one variation, one or more borate - based materials may have an ionic conductivity greater than or equal to about 10 -7 S / cm to less than or equal to about 10 -2 S / cm.

[0075] The nitride solid electrolyte is composed of nitride solid electrolyte particles, including Li3N, Li7PN4, LiSi2N3, LiPON, and combinations thereof. In one variation, one or more nitride-based materials may have a carbon content greater than or equal to about 10 -9 S / cm to an ionic conductivity of less than or equal to about 1 S / cm.

[0076] It is understandable that in the present application, there is no particular limitation on the positive electrode sheet, as long as it can function as the positive electrode of a solid battery as long as it complies with the overall inventive concept of the present application.

[0077] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer; the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer;

[0078] The positive electrode active material layer is arranged on both sides of the positive electrode current collector, and the negative electrode active material layer is arranged on both sides of the negative electrode current collector.

[0079] In some embodiments, the positive electrode active material layer includes a positive electrode active material, a positive electrode conductor, and a positive electrode binder. The negative electrode active material layer includes a negative electrode active material, a negative electrode conductor, and a negative electrode binder.

[0080] In some embodiments, the positive electrode current collector is not particularly limited, as long as it has conductivity and does not cause chemical changes in the solid-state battery. Specifically, copper, stainless steel, aluminum, nickel, titanium, or a metal current collector with a surface treated with carbon or other substances can be used.

[0081] In some embodiments, the positive electrode active material includes but is not limited to one or more of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganate, lithium nickel cobalt aluminum oxide, lithium-rich manganese base, elemental sulfur, sodium iron manganate, sodium iron titanate, sodium iron sulfate, sodium iron phosphate, sodium vanadium phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, and lithium titanate materials.

[0082] In some embodiments, the positive electrode conductor includes, but is not limited to, carbon-based materials, powdered nickel or other metal particles or conductive polymers. Carbon-based materials may include, for example, particles of carbon black, graphite, super-P, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly (3,4-ethylenedioxythiophene) polystyrene sulfonate, and the like.

[0083] In some embodiments, the positive electrode binder includes, but is not limited to, one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyoxymethylene (POM), polycarbonate (PC), polyamide (PA), acrylic plastics, other polyolefins and copolymers thereof, polysulfone, polyphenylene oxide (PPO) and carboxymethyl cellulose (CMC). Further, the binder is polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF).

[0084] It is understood that in the present application, there is no particular limitation on the negative electrode sheet, as long as it can function as the negative electrode of the solid battery under the premise of conforming to the overall inventive concept of the present application. The following is only exemplary, and the negative electrode sheet includes a negative electrode current collector, a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder.

[0085] In some embodiments, the shape of the negative electrode current collector includes any one of a foil shape, a plate shape, or a grid shape;

[0086] Further, the negative electrode current collector includes but is not limited to any one of aluminum, copper, nickel or zinc; optionally, the negative electrode current collector is copper, such as copper foil;

[0087] Furthermore, the negative electrode current collector includes any one of aluminum, copper, nickel or zinc alloy.

[0088] In some embodiments, the negative electrode active material includes, but is not limited to, one or more of graphite, silicon, silicon oxygen, silicon carbon, lithium titanate, hard carbon, soft carbon, tin oxide, and titanium dioxide materials.

[0089] In some embodiments, the negative electrode conductive agent includes, but is not limited to, carbon-based materials, powdered nickel or other metal particles or conductive polymers. Carbon-based materials may include, for example, particles of carbon black, graphite, super-P, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly (3,4-ethylenedioxythiophene) polystyrene sulfonate, and the like.

[0090] In some embodiments, the negative electrode binder includes, but is not limited to, one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyoxymethylene (POM), polycarbonate (PC), polyamide (PA), acrylic plastics, other polyolefins and copolymers thereof, polysulfone, polyphenylene oxide (PPO) and carboxymethyl cellulose (CMC). Further, the binder is polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF).

[0091] The present application also provides a method for preparing the core provided in the first aspect, comprising the following steps:

[0092] Mixing first solid electrolyte particles, first bonding particles and a first solvent to prepare a first solid electrolyte slurry;

[0093] Mixing polymer electrolyte particles, a conductor and a third solvent to prepare a mixed slurry;

[0094] Mixing second solid electrolyte particles, second binding particles and a second solvent to prepare a second solid electrolyte slurry;

[0095] Sequentially coating the first solid electrolyte slurry, the mixed slurry and the second solid electrolyte slurry on the surface of the first electrode piece;

[0096] Drying to form a solid electrolyte membrane on the surface of the first electrode; compounding the second electrode on the surface of the solid electrolyte membrane to obtain a laminate;

[0097] The laminate is wound to form a winding core.

[0098] In some embodiments, the number of winding layers of the core is 10 to 100, including but not limited to 10, 20, 30, 40, 50, 60, 70, 80, 90, 100. In some embodiments, the first solvent, the second solvent and the third solvent are the same, and are all selected from one or more of dimethylformamide, N,N-dimethylpyrrolidone, dimethyl sulfoxide, dimethylacetamide, diethyl carbonate, dimethyl carbonate, ethylene carbonate and the like.

[0099] In some of the embodiments, the slurry is coated on the surface of the electrode plate by a coating machine, and the final coating thickness can be controlled by adjusting the concentration of the slurry solution and / or the number of coatings.

[0100] It can be understood that different solid electrolyte membrane slurries can be prepared according to the actual needs of different areas of the solid electrolyte membrane (flat area 1, transition area 2, bending area 3), and then the different solid electrolyte membrane slurries can be coated on the surface of the electrode plate in different areas by a coating machine, thereby forming a solid electrolyte coating with intervals arranged in the flat area 1, transition area 2, and bending area 3 in the coating direction to obtain the final solid electrolyte membrane.

[0101] It is understood that the above-mentioned drying treatment step is a process for removing solvent and moisture from the slurry for drying the slurry coated on the electrode plate, which can be adjusted according to the different solvents used. For example, it is carried out in a vacuum oven at 50°C to 200°C. The drying method includes, for example, drying by warm air, hot air, low-humidity air, vacuum drying or irradiation with (far) infrared or electromagnetic radiation. The drying time is not particularly limited and is generally 30s to 24h. In some embodiments, the first pole piece is one of the positive pole piece and the negative pole piece, and the second pole piece is the other one.

[0102] In some embodiments, the method for preparing the core further comprises the following steps:

[0103] preparing a positive electrode sheet;

[0104] Prepare the negative electrode sheet.

[0105] It is understandable that in the present application, there is no particular limitation on the preparation method of the positive electrode sheet and the negative electrode sheet, and they can be easily manufactured by known methods under the premise of complying with the overall inventive concept of the present application.

[0106] In some embodiments, preparing the positive electrode sheet comprises the following steps:

[0107] The positive electrode active material, the positive electrode binder and the positive electrode conductive agent are mixed and added into a solvent to prepare a positive electrode slurry;

[0108] The positive electrode slurry is coated on the positive electrode current collector, and after drying and roll pressing, a positive electrode sheet is obtained.

[0109] The following is only for illustration: the positive electrode active material lithium manganese oxide, the binder PVDF, and the conductive agent Super-P are weighed in a mass ratio of 95:3:2, and mixed evenly by a jet mill, and the solvent NMP is added to form a uniform slurry. The slurry is coated on the surface of the aluminum foil current collector, dried, and pressed to form a positive electrode sheet.

[0110] In some embodiments, preparing the negative electrode sheet comprises the following steps:

[0111] The negative electrode active material, the negative electrode binder and the negative electrode conductive agent are mixed and added into a solvent to prepare a negative electrode slurry;

[0112] The negative electrode slurry is coated on the negative electrode current collector, and after drying and roll pressing, a negative electrode sheet is obtained.

[0113] The following is only for illustration: the negative electrode active material graphite, the binder PVDF, and the conductive agent Super-P are weighed in a mass ratio of 95:3:2, and mixed evenly by air flow milling, and the solvent NMP is added to form a uniform slurry, and the slurry is coated on the surface of the copper foil current collector, dried, and pressed to form a negative electrode sheet.

[0114] It is understandable that the present application does not specifically limit the type of solvent. Under the premise of satisfying the inventive concept of the present application, any known type of solvent can be applied to the present application. The following are merely illustrative examples rather than limitations on the scope of protection. For example, the solvent may be N-methylformamide (NMF).

[0115] In other embodiments, the positive electrode sheet and the negative electrode sheet may be prepared by a dry process. A second aspect of the present application provides a solid-state battery, the solid-state battery comprising the winding core provided by the first aspect.

[0116] In the present application, there is no particular limitation on the preparation process of the solid-state battery. Any known process method for preparing a wound solid-state battery can be used as long as the overall inventive concept of the present application is met.

[0117] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0118] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A winding core, characterized in that: The invention comprises a wound positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane arranged between the positive electrode sheet and the negative electrode sheet, wherein the solid electrolyte membrane comprises a flat area, a bending area, and a transition area connecting the flat area and the bending area; the transition area comprises an elastic layer; The bending angle of the flat area in the length direction of the winding core is ≤3°; The curvature radius of the transition zone is smaller than the curvature radius of the bending zone; The length of the transition zone in the length direction of the winding core is 1 mm to 10 mm.

2. The winding core according to claim 1, characterized in that: The thickness of the solid electrolyte membrane is 1 μm to 100 μm.

3. The winding core according to claim 1, characterized in that: The thickness of the elastic layer gradually increases from the outer layer to the inner layer of the winding core.

4. The winding core according to claim 1, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer; The positive electrode active material layer is arranged on both sides of the positive electrode current collector, and the negative electrode active material layer is arranged on both sides of the negative electrode current collector.

5. The winding core according to claim 1, characterized in that: In each layer of the winding core, the area of ​​the elastic layer accounts for 5% to 30% of the sum of the areas of the transition zone and the bending zone.

6. The winding core according to claim 1, characterized in that: In each layer of the winding core, the thicknesses of the flat area, the transition area and the bending area are the same.

7. The winding core according to claim 1, characterized in that: The length of the transition zone in the length direction of the winding core gradually decreases from the outer layer to the inner layer of the winding core.

8. The winding core according to claim 7, characterized in that: From the outer layer to the inner layer of the winding core, the area of ​​the flat area is the same, and the length of the bending area in the circumferential direction of the winding core gradually decreases.

9. The winding core according to claim 1, characterized in that: The winding core has 10 to 100 layers.

10. A solid-state battery, characterized in that: The winding core comprises the winding core as described in any one of claims 1 to 9.